Analysis of coping strategies against stresses of future professionals of socionomy occupations - Dubchak, Halyna (Social Welfare: Interdisciplinary Approach, 2016)
The article discusses the issue of tolerance to stress of future specialists with socionomy occupations. The results of the performed empirical study of behavioural coping strategies against stresses, levels of psychic tension and stress tolerance of modern Ukrainian students from universities and vocational schools are described